Designing Biology Lab manuals Based on Local Resources to Enhance Critical Thingking Skills - Siska Dwi Anggraini; Imas Cintamulya (Integrated Science Education Journal, 2026)
Purpose of the study: Biology learning in the 21st century requires innovative, contextual learning resources that support students’ critical thinking skills. However, electronic biology practicum instructions that integrate local potential are still limited in biology education. Therefore, this study aimed to develop and validate local-potential-based electronic biology practicum instructions using Moringa oleifera L. leaf extract to assess its effects on Allium cepa L. growth and support students’ critical thinking skills. Methodology: This study employed the Research and Development (R&D) method using the 4D model; however, the research was limited to the development stage. The developed product was an electronic biology practicum instruction that integrated local potential by using Moringa oleifera leaf extract. Product validity data were collected using validation sheets assessed by three expert validators covering aspects of material, systematic presentation, language, and graphics. Main Findings: The results showed that the average validity score was 90.8%, indicating it is very valid. The validity details included the material aspect (91.6%), systematic presentation aspect (90%), language aspect (88.5%), and graphic aspect (93.3%). These findings indicate that the developed electronic practicum instructions met the validity criteria and are suitable for use in biology learning. Novelty/Originality of this study: The novelty of this study lies in integrating local potential and digital technology into electronic biology practicum instruction to create a more contextual and meaningful learning experience. In addition, the developed product has implications for supporting students’ critical thinking skills and for promoting contextual biology learning relevant to students' daily lives.